(untitled) (REVISTA NODO, 2008)
The growing attendance of indigenous students to public and private universities in Bogota has brought about innovative spaces for intercultural discussion that take on new ways of educating, narrating and researching reality, from the crossing of western thought and ancient knowledge of the country´s native cultures. Within this context, the article presents a research methodology for intercultural studies that takes into account Colombia´s cultural diversity and characteristic race mixes, as a contribution to the processes of contact, dialogue and coexistence that we have named here "multicultural interactions".